1996
DOI: 10.1055/s-2007-972849
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Reproducibility of Performance Testing on an Air-Braked Cycle Ergometer

Abstract: The purposes of this study were (I) to assess the reproducibility of endurance performance testing on an air-braked cycle ergometer, and (II) to compare laboratory performances to performances in road races. Ten well-trained, competitive cyclists (peak power output [PPO] 443 +/- 37 W, [values are mean +/- SD]) undertook either: (I) three 20 km and three 40 km time trials (TT) on an air braked ergometry system (Kingcycle) (n = 6), and/or (II) three 40 km laboratory TT and two 40 km road TT competitions (n = 8).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
111
2

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(133 citation statements)
references
References 1 publication
(1 reference statement)
20
111
2
Order By: Relevance
“…This system, which has previously been described in full (Palmer et al 1996), allows the participant to exercise on their own bicycle against a resistance comparable to that of riding on the road. This system has been shown to be both valid and reliable during 20, 40 km (Palmer et al 1996) and max-test protocols (Keen et al 1991).…”
Section: Laboratory Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…This system, which has previously been described in full (Palmer et al 1996), allows the participant to exercise on their own bicycle against a resistance comparable to that of riding on the road. This system has been shown to be both valid and reliable during 20, 40 km (Palmer et al 1996) and max-test protocols (Keen et al 1991).…”
Section: Laboratory Testingmentioning
confidence: 99%
“…Following standardised calibration procedures (Palmer et al 1996), participants carried out a warm-up at a self-selected intensity for 10 min. Immediately following this, the maximal test was initiated at a workload of 150-200 W. Thereafter, workload increased at a ramp rate of 20 W min À1 (1 W every 3 s).…”
Section: Laboratory Testingmentioning
confidence: 99%
“…Even using welltrained cyclists, Jeukendrup et al [23] reported CoV values ranging between 17 and 40%. In contrast with TTE protocols, testing protocols that employ a fixed quantity of work, distance or time are reported to be more reliable [2,17,23,28,33,34]. However, we recognise that in conducting the present study we have based our field estimates of CP on laboratory estimates derived through TTE protocols.…”
mentioning
confidence: 93%
“…However, despite the ecological validity of laboratory based testing acknowledged within cycling as a whole, there still remains some dispute between individual cycling disciplines (20,22,9).…”
Section: Introductionmentioning
confidence: 99%